Hypoxic sleep study - Garvican-Lewis, L. A.; Clark, S. A.; Polglaze, T.; McFadden, G.; Gore, C. J. (Box Altitude, 2018)
Over 6 months, 11 players completed three normobaric LHTL exposures (block 1:11 days at 3000 m; block 2+3:9 days at 2500 m, 11 days normoxia, 10 days at 2800 m). Haemoglobin mass (Hbmass) was measured through carbon monoxide-rebreathing. Before each block, the relationship between Hbmass and water polo-specific aerobic fitness was investigated using the Multistage Shuttle Swim Test (MSST). Effect size statistics were adopted with likely, highly likely and almost certainly results being >75%, >95%, >99%, respectively. A Pearson product moment correlation was used to characterise the association between pooled data of Hbmass and MSST. Results: Hbmass (mean±SD, pre 721±66 g) likely increased after block 1 and almost certainly after block 2+3 (% change; 90% confidence limits: block 1: 3.7%; 1.3-6.2%, block 2+3: 4.5%; 3.8-5.1%) and the net effect was almost certainly higher after block 2+3 than before block 1 (pre) by 8.5%; 7.3-9.7%. There was a very large correlation between Hbmass (g/kg) and MSST score (r=0.73). Conclusions: LHTL exposures of <2 weeks induced approximately 4% increase in Hbmass of water polo players. Extra Hbmass may increase aerobic power, but since match performance is nuanced by many factors it is impossible to ascertain whether the increased Hbmass contributed to Australia`s Bronze medal.